The EU engagement in democracy promotion in post-Soviet Central Asia: the case study of the Kyrgyz Republic – prospects and challenges - Kainazarov, Baktybek (Przegląd Politologiczny, 2018)
When Soviet Union collapsed, there were different hypothesis regarding democratic reforms and political system changes in Kyrgyzstan. It was believed that Kyrgyzstan would develop its independent policy and democratic governance. Since early 1990s European countries through OSCE, and later through the EU launched development projects have been playing central role in democracy promotion and civil society development in Central Asia. At the same time, as analysis show geopolitical interests of neighboring powerful states such as Russia and China increased in the region, which resulted the creation of regional institutions such as Shanhai Cooperation Organization (SCO), Collective Security Organization (CSO), Eurasian Economic Union (EEU) and Silk Road Belt Initiative (SRBI). While being the fully-fledged member of China and Russia led regional institutions, Kyrgyzstan is under heavy political and economic influence. Besides, human rights situation in Kyrgyzstan like in other Central Asian countries has been deteriorating for last few years. Thus, the research paper focuses on interplay between Russia and China for geopolitical dominance in the region, including how it negatively influences for political volatility, civil society suppression and deterioration of human rights issues. Paper equally analyzes European countries engagement in human rights and democracy promotion in Kyrgyzstan. The research considers important to analyze the EU strategy in democratic reforms in Central Asia and to investigate why it matters for the EU.